Estado nutricional e prognóstico de crianças gravemente doentes - Menezes, Fernanda Souza de [UNIFESP] (2010)
Background & aims:the prognostic implications of severe disease-related malnutrition have not been clarifiedThis study aimed to determine the prevalence of malnutrition on admission and whether this nutritional disorder is associated with the prognosis of children admitted to a pediatric intensive care unit (PICU). Methods: In a prospective cohort study, 385 children were assessed regarding nutritional status at admission and clinical outcome. The outcome variables were: 30-day mortality, length of PICU stay and duration of mechanical ventilation. Potential outcome variables were: gender, age, diagnosis (clinical, surgical, cardiac disease), septic shock, malnutrition, scores Pediatric Index of Mortality – PIM2 and Pediatric Logistic Organ Dysfunction - PELOD. Patients with a z score < -2 of expected weight for age, length for age or body mass index were considered malnourished. Results: 45.5% of patients were malnourished on admission. Malnutrition was associated with higher length of mechanical ventilation and length of PICU stay, and not with mortality in the univariate analysis. There was association with length of mechanical ventilation in the logistic regression model (OR 1.76, 95% confidence interval 1.08-2.88; p=0.024). Conclusions: The prevalence of malnutrition at admission was high. Malnutrition was not a predictive factor for mortality but showed independent association with length of mechanical ventilation.